Patient perceptions and preferences during a community-based telehealth care model for moderate-to-severe hypertension in rural communities in Kenya and Uganda - Jason Johnson-Peretz; Andrew Mutabazi; Ambrose Byamukama; Lawrence Owino; Cecilia Akatukwasa; Anjeline Onyango; Fredrick Atwine; Titus O. Arunga; Sabina Ogachi; Asiphas Owaraganise; Norton Sang; Erick M. Wafula; et al. (PLoS ONE, 2026)
Introduction Hypertension is a growing health concern in sub-Saharan Africa, yet access to care can be challenging, especially in rural areas. Overcoming barriers to hypertension care remains a priority. Pairing community health worker (CHW) and telehealth modalities offers one way to extend the reach of hypertension care without overburdening patients or healthcare systems in rural areas. Methods This qualitative study was nested within the SEARCH Sapphire pilot randomised controlled trial testing hypertension treatment through CHW-facilitated, clinician-driven telehealth (intervention) compared to clinic-based care (control) for adults aged ≥40 years with moderate-severe hypertension in rural western Kenya and southwestern Uganda. We conducted audio-recorded, in-depth, semi-structured interviews with purposively selected healthcare providers (clinicians and CHWs; N = 15) and participants (N = 40) between January-April 2023 to explore hypertension diagnosis and linkage to care; experiences with community hypertension care; family and work contexts; and the integration of telehealth into clinic and CHW workflows. Results Overall, participants felt satisfied with community-delivered telehealth care for hypertension. Participants noted community-based care saved on transport costs and reached those who were unwell or who lived far from clinic. Intervention arm participants felt CHWs were suitable for routine hypertension care, worked closely with clinicians, and could increase health literacy within the community. Participants desired a model with clear communication and involvement of the facility-based clinician, CHW, and participant. Providers found telehealth to be of similar quality to clinic-based care for routine hypertension treatment, though noted that clinic-based care is at times needed for more comprehensive clinical evaluation or to provide additional healthcare services. Conclusions Participants and providers indicated overall positive attitudes and receptivity to CHW-facilitated telehealth for hypertension care. CHW-delivered telehealth for community-based hypertension care offers one way to improve hypertension treatment outcomes in a manner that prioritizes patient-centeredness and maintains care quality. Trial Registration NCT04810650 Registered on 2021-03-18.